Respuesta :
3x is the miles from downstream
4 (x - 1) is the return trip
Solution:
3x = 4 (x - 1)
3x =4x - 4
-x = -4
x = 4
The outward journey 3x = 12 miles
Return journey is same length
Therefore the distance travel is 24 miles
4 (x - 1) is the return trip
Solution:
3x = 4 (x - 1)
3x =4x - 4
-x = -4
x = 4
The outward journey 3x = 12 miles
Return journey is same length
Therefore the distance travel is 24 miles
Answer:
The answer is 24 miles.
Step-by-step explanation:
We know that distance = rate * time
Length of the journey = [tex]3x[/tex] from downstream
Length of the journey = [tex]4(x-1)[/tex] from return trip
As the distance is same, we will equate both the journey lengths.
[tex]3x= 4(x-1)[/tex]
Solving for x;
[tex]3x=4x-4[/tex]
[tex]-x=-4[/tex]
x = 4
Thus the forward journey, [tex]3x=3(4)[/tex] = 12 miles.
Return journey will be of same length that is 12 miles.
The total distance traveled is [tex]12+12=24[/tex] miles.
Therefore, the answer is 24 miles.